2015
DOI: 10.1371/journal.pone.0121739
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Caspase-Cleaved Cytokeratin-18 in Patients with Severe Traumatic Brain Injury Are Associated with Mortality: A Pilot Study

Abstract: ObjectiveThere have been found apoptotic changes in brain tissue samples from animals and humans after a traumatic brain injury (TBI). The protein cytokeratin 18 (CK-18), present in epithelial cells, is cleaved by the action of caspases during apoptosis, and the resulting fragments are released into the blood as caspase-cleaved CK (CCCK)-18. Circulating levels of CCCK-18, as biomarker of apoptosis, have been determined in patients with different processes; however, it has not been explored in TBI patients. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…However, it should be emphasized that K18 and its caspase‐cleaved fragments detected in the circulation are not necessarily liver origin since K18 is also the major intermediate filaments of epithelial cells other than hepatocytes . Serum cK18 was significantly increased in patients with traumatic brain injury and malignant middle cerebral artery infarction . Therefore, our observation that the significantly higher level of serum K18 in patients with HE than that in those without HE was reasonable.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, it should be emphasized that K18 and its caspase‐cleaved fragments detected in the circulation are not necessarily liver origin since K18 is also the major intermediate filaments of epithelial cells other than hepatocytes . Serum cK18 was significantly increased in patients with traumatic brain injury and malignant middle cerebral artery infarction . Therefore, our observation that the significantly higher level of serum K18 in patients with HE than that in those without HE was reasonable.…”
Section: Discussionmentioning
confidence: 62%
“…9 Serum cK18 was significantly increased in patients with traumatic brain injury and malignant middle cerebral artery infarction. 44,45 Therefore, our observation that the significantly higher level of serum K18 in patients with HE than that in those without HE was reasonable. However, such observation was not confirmed when similar analysis was performed only in patients without liver failure.…”
Section: Changes Of Cell Death Biomarkers In Relation To Outcomementioning
confidence: 55%
“…For example, Lorente et al showed that there is an association between early mortality and higher serum CCCK-18 levels in severe spontaneous intracerebral hemorrhage patients (22). They also showed that there are higher serum CCCK-18 levels in cases of severe malignant middle cerebral artery infarction, severe sepsis and severe traumatic brain injury (6,23,24). Besides that, Gu et al suggested that there is an association between increased serum CCCK-18 concentrations and late mortality in intracerebral hemorrhage (25).…”
Section: Discussionmentioning
confidence: 99%
“…A very effective tool to evaluate the brain function in these conditions is electroencephalography (EEG). However, a dynamical evolution of injury is commonly observed in critically ill patients, due to the occurrence of epileptic seizures (ES), status epilepticus (SE), apoptosis, vasospasm or other different brain insults [2][3][4]. In this sense, continuous EEG (cEEG) is a non-invasive method that allows the functional assessment of the cerebral cortex in real time for prolonged periods of time.…”
Section: Introductionmentioning
confidence: 99%